2008
DOI: 10.1177/000312240807300604
|View full text |Cite
|
Sign up to set email alerts
|

Love, Sex, and Crime: Adolescent Romantic Relationships and Offending

Abstract: Scholars are often pessimistic about adolescent dating, linking it to increases in depression, interpersonal violence, conflict with parents, school failure, associations with delinquents, substance use, and offending. Yet, the various dimensions of dating may have opposing consequences. The closeness offered by adolescent romantic love may fill an important void found between the weakening of bonds with parents and the onset of adult attachments, and it may discourage an array of negative outcomes, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 52 publications
7
88
2
2
Order By: Relevance
“…Double standards are understood in that case as the persistence of a desire toward men who have power but not ethical values, and, on the other hand, the maintenance of a feeling of friendship toward men that have egalitarian and solidary attitudes but without power positions (Gomez, 2015). McCarthy and Casey (2008) coincide with this analysis and they indicate an attraction toward violence in young cohorts. These authors also pay attention on the role that family has on this link and they argued that some young people feel their relationship with their parents is weakening, so they seek to fill this emotional void with partners associated with violence.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Double standards are understood in that case as the persistence of a desire toward men who have power but not ethical values, and, on the other hand, the maintenance of a feeling of friendship toward men that have egalitarian and solidary attitudes but without power positions (Gomez, 2015). McCarthy and Casey (2008) coincide with this analysis and they indicate an attraction toward violence in young cohorts. These authors also pay attention on the role that family has on this link and they argued that some young people feel their relationship with their parents is weakening, so they seek to fill this emotional void with partners associated with violence.…”
Section: Introductionmentioning
confidence: 71%
“…In addition, in those analyses the role that family environment and language have in these processes is evidenced. For instance, the literature helps reveal how conceptions of attractiveness are defined through daily interactions in different socializing spaces like family (Duque, 2006;Urpí and Naval, 2006;McCarthy and Casey, 2008;Gomez, 2015). Similarly, it also helps to comprehend how the construction of gender identity and people's emotions perpetuate affective and sexual relationships marked by the attraction toward violence (Kimmel, 2000;Connell, 2005;Schrock and Schwalbe, 2009;Hughey, 2011;Hunter et al, 2011;Shaffer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Being isolate in the friendship network signifies low status within the class. As status is an important asset to be successful in dating (McCarthy & Casey 2008), students may form their preferences accordingly, to avoid disappointments. Thus, relatively low status members of the majority (high status) group will be willing to choose partners from the minority (low status) groups.…”
Section: Discussionmentioning
confidence: 99%
“…Possible moderators that could be examined include the following: individual-level factors such as personality, attachment styles, communication skills, motivations (Vrangalova, 2015b); negative social or health hookup consequences (Napper et al, 2016); and contextual factors such as social norms, peer pressure, coercion, or relationship breakups. Identifying other variables that may be associated with alcohol and drug use, such as delinquency, poorer grades, and truancy (e.g., McCarthy & Casey, 2008), would be useful to verify whether CSREs are part of a constellation of externalizing problems. General selfesteem was not associated with engagement in CSREs in our study, but a measure of sexual self-esteem could be interesting to examine among boys and girls.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Alcohol use has been considered to be a strong predictor of CSREs (Johnson, 2013), but few studies have investigated substance use as a consequence of CSREs. A representative prospective study among 12-to 18-year-olds reported that casual sex was associated with a significant increase in substance use, including cigarettes, alcohol, marijuana, cocaine and other illegal drugs, over one year (McCarthy & Casey, 2008). Gender differences were not studied.…”
mentioning
confidence: 99%